2020
DOI: 10.1002/smll.202000527
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Similarities between 3D Human Bronchial Epithelium and Mice Lung, Exposed to Copper Oxide Nanoparticles, Support Non‐Animal Methods for Hazard Assessment

Abstract: The diversity and increasing prevalence of products derived from engineered nanomaterials (ENM), warrants implementation of non‐animal approaches to health hazard assessment for ethical and practical reasons. Although non‐animal approaches are becoming increasingly popular, there are almost no studies of side‐by‐side comparisons with traditional in vivo assays. Here, transcriptomics is used to investigate mechanistic similarities between healthy/asthmatic models of 3D air–liquid interface (ALI) cultures of don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In vitro models based on pulmonary cells represent excellent tools to study lung toxicity induced by exposure to ENMs. Immortalized or tumorigenic cell lines (A549, BEAS-2B, and Calu-3) are routinely used as monolayer models [ 39 ] or in co-culture with immune cells (e.g., differentiated THP-1) to study inflammatory responses induced by ENM exposure [ 40 , 41 ]. These in vitro models can be used both in submerged conditions or at the Air–Liquid Interface (ALI), which has been demonstrated to favor a better interaction between NPs and cells and has been considered physiologically more relevant for inhaled NPs research [ 32 , 40 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro models based on pulmonary cells represent excellent tools to study lung toxicity induced by exposure to ENMs. Immortalized or tumorigenic cell lines (A549, BEAS-2B, and Calu-3) are routinely used as monolayer models [ 39 ] or in co-culture with immune cells (e.g., differentiated THP-1) to study inflammatory responses induced by ENM exposure [ 40 , 41 ]. These in vitro models can be used both in submerged conditions or at the Air–Liquid Interface (ALI), which has been demonstrated to favor a better interaction between NPs and cells and has been considered physiologically more relevant for inhaled NPs research [ 32 , 40 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Others have also found a higher sensitivity of cells exposed at the ALI compared to submerged exposure experiments [41,44,45]. Therefore, exposure of cells at the air-liquid interface has been shown to be a valid and sensitive method to assess the toxicity of several poorly soluble nanomaterials in monocultures and co-cultures and could bridge the gap between traditional 2D in vitro assays and animal models of airway exposure [4,27,39,44,[46][47][48][49][50][51].…”
Section: In Vitro Modelsmentioning
confidence: 99%
“…Only 19% of mouse lung genes with human orthologues were not expressed in the 3D ALI model. It demonstrated 3D ALI models based on epithelial cells reduce the gap between traditional 2D in vitro assays and animal models [11]. However, this study directly exposed the tissues to the test chemicals, which could not account for the characteristics of inhalation exposure.…”
Section: Introductionmentioning
confidence: 95%
“…Indeed, many in vitro test methods have been studied to evaluate the inhalation toxicity of chemicals [9][10][11][12]. A previous study demonstrated that an in vitro three-dimensional human airway model (Epi-Airway TM ) combined with multiple endpoint analysis (histology, viability, intracellular glutathione (GSH) levels, and mRNA expression) could provide a robust model for evaluating various types of respiratory toxicity.…”
Section: Introductionmentioning
confidence: 99%